Influence of Gender Role Attitude, Quality of Alternatives, Investment Size, and Commitment on Marital Satisfaction between Thai Women Who Married Thai Men and Thai Women Who Married Foreign Men - Suntornkanit, Napont; Varma, Parvathy (Scholar: Human Sciences, 2018)
Gender role attitude, quality of alternatives, investment size, commitment, and marital satisfaction were measured and compared between Thai women who married Thai men and Thai women who married foreign men. Direct and indirect influences of gender role attitude, quality of alternatives, investment size, and commitment on marital satisfaction were also analyzed. The sample consisted of 200 respondents (N=200), of whom 100 were Thai women who married Thai men (50%) and 100 were Thai women who married foreign men (50%). The mean age of respondents was 35 years, ranging from 21 years to 58 years, and the mean age of their husbands was 39 years, ranging from 26 years to 60 years. Results indicated that Thai women who married foreign men have higher level of marital satisfaction, higher commitment, and lower quality of alternatives. There is no significant difference in gender role attitude and investment size. Path analyses produced similar results between the two groups of women in that there are no direct influences of gender role attitude, quality of alternatives, and investment size on marital satisfaction. However, an indirect influence between quality of alternatives and investment size on marital satisfaction emerged when mediated by commitment. Gender role attitude was found to have an indirect influence when mediated with commitment, only for the group of women who married foreign men. Both models, however, indicated that commitment is a significant predictor of marital satisfaction.